Perencanaan dan Perhitungan Beban Instalasi Listrik pada Rumah Tinggal Tipe Prototipe dengan Luas 11 × 19 Meter - Khalsum, Ummu; Zain, Nurmayanti (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2026)
This study aims to analyze and design the electrical installation requirements for a prototype residential building with dimensions of 11 × 19 meters. The research applies a technical calculation approach based on lighting standards, air conditioning capacity estimation, load analysis, and electrical protection planning. Lighting requirements were determined using the lumen method by considering room area, illumination standards, coefficient of utilization, and light loss factor. Air conditioning capacity was calculated based on room area and standard cooling load values in BTU/hr. Furthermore, total electrical loads were analyzed to determine installed capacity, nominal current, Miniature Circuit Breaker (MCB) ratings, and appropriate cable cross-sectional areas with safety factors applied. The results indicate that proper load grouping, appropriate MCB selection, and correct cable sizing significantly enhance system safety and reliability. The study provides a systematic planning model for residential electrical installations that meets safety, efficiency, and technical standards, and can serve as a reference for similar residential building designs.